Duck Tembusu Virus Utilizes miR-221-3p Expression to Facilitate Viral Replication via Targeting of Suppressor of Cytokine Signaling 5 - Cui, Min; Chen, Shuling; Zhang, Shaqiu; Cheng, Anchun; Pan, Yuhong; Huang, Juan; Hu, Zhiqiang; Zhang, Xingcui; Wang, Mingshu; Zhu, Dekang; Chen, Shun; Liu, Mafeng; et al. (Frontiers in Microbiology, 2020)
Duck Tembusu Virus (DTMUV), a member of Flaviviridae family, causes acute eggdrop syndrome in ducks. MicroRNAs (miRNAs) have been found to be involved in various biological processes, including tumor genesis, viral infection and immune response. However, the functional effect of miRNAs on DTMUV replication remains largely unclear. This study aimed to elucidate the role of host microRNA-221-3p (miR-221-3p) in regulating DTMUV replication. Here, we indicated the expression of miR-221-3p was significantly upregulated in duck embryo fibroblasts (DEF) during DTMUV infection. Transfection of miR-221-3p mimic significantly reduced IFN-β production, while transfection of miR-221-3p inhibitor conversely significantly increased the expression of IFN-β in DTMUV-infected DEF. Moreover, we found that viral RNA copies, viral E protein expression level and virus titer which represent the replication and proliferation of virus, were all enhanced when transfecting the miR-221-3p mimic into DEF, reverse results were also observed by transfecting the miR-221-3p inhibitor. We also found that the expression of suppressors of cytokine signaling 5 (SOCS5) was downregulated in DEF infected with DTMUV. In addition, we further proved that SOCS5 is a target of miR-221-3p, and miR-221-3p could negatively modulate SOCS5 expression both at mRNA and protein levels. Finally, our results showed that overexpression of SOCS5 inhibited DTMUV replication and knockdown of SOCS5 enhanced DTMUV replication. Thus, our findings reveal a novel host evasion mechanism adopted by DTMUV via miR-221-3p, which may hew out novel strategies for designing miRNA-based vaccines and therapies.